Usulan Perbaikan Kualitas Defect pada Proses Seal di Bagian Solid Quarter (Studi Kasus Perusahaan Automotive Rubber) - Tosty Maylangi Sitorus; Anggy Fitria Sari; Septia Supandi (Universitas Mercu Buana, 2020)
Quality improvement approaches and methodologies have been developed through previousresearch. This study proposes quality improvement for automotive rubber companies as a casestudy in which the largest percentage of NGs in item-B in the seal, compact / quarterlydepartments during the January-June 2019 period was found. Based on the results of the studythere are differences, initially suspected and explained through the P control map, that is, thereis a point outside the control limit (UCL), which is the 20th observation. Identify possible causesof inaccuracy in 5 factors, namely (low engine temperature, decreased engine pressure, andcompressor mold holes), method (giving toluene liquid in mold before inserting material atmaturity), material (less material coating and end of profile cuts or dirty joints), people(pursuing production targets and new employees who are still in job training), environment(night lighting). Get repair with 5W + 1H method.